Assessment of yield and yield attributes of wheat varieties under different date of sowing in Madhesh Province of Nepal - Pokhrel, Nishchal; Neupane, Bipin; Dhungana, Prakash; Subedi, Deependra; Puri, Kiran; Bhattarai, Nitesh; Shrestha, Abhisek (Nepal Agriculture Research Journal, 2025)
Wheat (Triticum aestivum L.) contributes to a vital portion of the global food supply and is an economically important crop. Sowing time and suitable varieties are important factors in attaining higher yields. Thus, an experiment was conducted at the Field of CNRM Bardibas in Madhesh Province during the winter of 2023-24 to assess the impact of different sowing dates and wheat varieties. The experiment designed in a split-plot design with two replications, involved three sowing dates (13 December, 23 December, 2 January) as main plot treatment and eight varieties (Banganga, Zinc Gahun 1, Gautam, BL 4341, Borlaug 2020, NL 1386, NL 1349, and  BL 4818) as sub-plot. Yield and yield attributes were taken at the time of harvest and during the growing season and then analyzed with Genstat ver. 15.1. The results revealed that sowing time and varieties showed a significant impact on yield and yield attributes. Among tested varieties, the highest yield was recorded in Banganga (3.94 t ha-1), and the least at Borlaug 2020 (2.79 t ha-1) and varied in yield up to 4-20% as compared to late sown. On Interaction (V*S), Banganga planted earlier provided a higher yield (4.59 t ha-1) followed by the same variety planted on 23 December, NL 1349 sown on 13 and 23 December. Banganga on 13 December (51.3 g) showed significantly higher TGW followed by NL 1349 (50.89) and the least in BL 4341 (34.8 g) under late sown. In conclusion, Banganga should be planted earlier to attain higher yields and further research must be carried out in the farmer's field for validation.